SISTEM INFORMASI LAYANAN CONTENT CREATOR PADA BANDHAWA PROJECT BERBASIS WEB - Wibowo, Yuniar Satrio; Chamid, Ahmad Abdul; Murti, Alif Catur (Universitas Muria Kudus, 2025)
ABSTRACT The development of service has turned into online media, to make it easier for customers and employees to managew work. In the case of the Bandhawa Project which includes digital marketing design services, sales are no tvery effective. The aim of the research is to build a service system entitled Grapich Design Service Sales Information System for Web-Based Bandhawa Project Vendors. Build web applications to claim business progress, including transaction facility services for customers. Therefore it can be concluded that the development of service sales information systems can facilitate the implementation of transactions by customers. Keywords : Information Systems, Graphic Design, Sales